Before she was my grandmother - Potter, Giselle (Enchanted Lion Books, 2025)
"From celebrated illustrator Giselle Potter, a beautiful and memorable story about the special bond between a grandparent and a grandchild. Whenever I visit my grandmother Alice, we love sitting together and telling each other stories. My favorite part is when she takes out her box of special things and we pass them back and forth. Each object -- a doll, a sketchbook, shells and stones, and more -- is a clue to a bigger story: the story of her life before she was my grandmother. Before she was my grandmother, she too was a young girl, with a life very different from my own. Little by little, the stories she tells and the objects she shares from her memory box reveal the many facets of her life, along with her great spirit, with its many colors and tones. Written and illustrated by the award-winning picture book maker Giselle Potter, Before she was my Grandmother celebrates strong and loving family connections, as well as the little moments and mementos of childhood that we carry with us all our lives -- and pass on to the next generation. It's also a touching reminder of how every life is so much richer and more multifaceted than any single identity or role."-- Provided by publisher.